Bioactivity of plants used traditionally in the treatment and management of men’s sexual health - Tsumbedzo Nemandalali; Monde A. Nyila; Thilivhali E. Tshikalange (Journal of Medicinal Plants for Economic Development)
Background: In many African societies, men still rely on the long cultural history of utilising medicinal plants to treat and manage their sexual health.